2010
DOI: 10.1007/s10903-010-9367-z
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and Reproductive Health Behaviors of Undocumented Migrants in Geneva: A Cross Sectional Study

Abstract: Undocumented migrants face major barriers in accessing prevention and health care. Whereas the association between low socioeconomic status and poor health is well documented only few studies have addressed specific health issues in undocumented migrants. The aim of the present study is to describe sexual and reproductive health behaviors of undocumented migrants in Geneva. This descriptive cross sectional study included consecutive undocumented migrants presenting from November 2007 to February 2008 to a heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Despite SRH being an important aspect of women’s quality of life, the utilisation of these services by refugee and migrant women is low, leading to negative SRH outcomes [4, 5]. For example, Sebo and colleagues [6] found that utilization of family planning methods and STI prevention were low among undocumented migrant women. Refugee women have also been shown to experience higher rates of unplanned pregnancy compared with women of host countries [7] due to lack of appropriate health information and low utilisation of contraceptives [8].…”
Section: Introductionmentioning
confidence: 99%
“…Despite SRH being an important aspect of women’s quality of life, the utilisation of these services by refugee and migrant women is low, leading to negative SRH outcomes [4, 5]. For example, Sebo and colleagues [6] found that utilization of family planning methods and STI prevention were low among undocumented migrant women. Refugee women have also been shown to experience higher rates of unplanned pregnancy compared with women of host countries [7] due to lack of appropriate health information and low utilisation of contraceptives [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several classifications have attempted to clarify the complex situation of access to care for IM [1,10,15]. The NowHereland project identified three categories of health care entitlement for IM in the EU: "no rights", "minimum rights", and "rights" [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…This research emphasis holds true for undocumented migrants in Switzerland: Bodenmann et al (2009) show that out of 125 screened undocumented migrants, 19.2% had a latent tuberculosis infection. Sebo et al (2011) and Casillas et al (2015) examine the sexual and reproductive health behaviour of undocumented women and discover low levels of contraceptive use and correspondingly high rates of unplanned pregnancies.…”
Section: Undocumented Migrants' Healthmentioning
confidence: 99%